Seasonal Variation in Antibacterial Activity of Bangladeshi Honey Against Five Pathogenic Bacteria (Bangladesh Journal of Genetics and Biotechnology, 2008)
No abstract available.Key words: Honey; antibacterial activity; pathogen; gram positive; gram negative Bangladesh j. genet. biotechnol. 6 (1&2): 55-58, 2005 (June & December)